Exploring the Role of IL-17A in Oral Dysbiosis-Associated Periodontitis and Its Correlation with Systemic Inflammatory Disease - Koichiro Irie; Tetsuji Azuma; Takaaki Tomofuji; Tatsuo Yamamoto (MDPI AG, 2023)
Oral microbiota play a pivotal role in maintaining homeostasis, safeguarding the oral cavity, and preventing the onset of disease. Oral dysbiosis has the potential to trigger pro-inflammatory effects and immune dysregulation, which can have a negative impact on systemic health. It is regarded as a key etiological factor for periodontitis. The emergence and persistence of oral dysbiosis have been demonstrated to mediate inflammatory pathology locally and at distant sites. The heightened inflammation observed in oral dysbiosis is dependent upon the secretion of interleukin-17A (IL-17A) by various innate and adaptive immune cells. IL-17A has been found to play a significant role in host defense mechanisms by inducing antibacterial peptides, recruiting neutrophils, and promoting local inflammation via cytokines and chemokines. This review seeks to present the current knowledge on oral dysbiosis and its prevention, as well as the underlying role of IL-17A in periodontitis induced by oral dysbiosis and its impact on systemic inflammatory disease.